THE HIGHER EDUCATION CHALLENGES THAT IMPACT SERVICE QUALITY IN LEBANESE PRIVATE UNIVERSITIES (Costos y Gestión, 2021)
In the context of globalization, privatization and liberalization, major changes occurred in the educationalenvironment, thus redefining the metrics of excellence for Higher Education. Fierce competition has pusheduniversities to gradually grant more importance to marketization of education which lead to the repositioningof Higher Education as a global commodity.This caused a paradigm shift, where main drivers of the lucrative business sphere were adopted by universities.The educational industry is since witnessing many reforms where the center of gravity shifted fromquality to quantity, therefore transforming the elite model into a mass education system. The commercializationof education contributed in watering down the academic rigor causing a conflict between administratorsand academics. Such strategic misalignment impacted the quality assurance’s purpose of yielding a favorableacademic environment.This paper is concerned with improving the students’ learning and quality of services in the private highereducation sector. Socio-Economic Approach to Management is pursued to help universities better balancebetween their external and internal environments. This intervention research focuses on enhancing the managementand quality of services to achieve higher sustainability and performance by transforming hiddencosts into added-value. The SEAM research methodology goes through the steps that compose the HORIVERTprocess which is composed of 2 main actions, horizontal and vertical. As a result, cohesive findings are createdwhere a full range of qualitative, quantitative and financial information are covered whereby social,economic and financial organizational objectives become integrated with.Based on the intervention results, we conclude that the quality of services teaching and curriculum quality,as well as academic and career counseling services, constitute important determinants of perceived servicequality and the influence of the latter construct over student satisfaction.
Keywords: Socio-Economic Approach to Management; Hidden Costs; Commercialization of Higher Education; Student Satisfaction